2017
DOI: 10.1016/j.cub.2017.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Theta Phase Synchronization Is the Glue that Binds Human Associative Memory

Abstract: Episodic memories are information-rich, often multisensory events that rely on binding different elements [1]. The elements that will constitute a memory episode are processed in specialized but distinct brain modules. The binding of these elements is most likely mediated by fast-acting long-term potentiation (LTP), which relies on the precise timing of neural activity [2]. Theta oscillations in the hippocampus orchestrate such timing as demonstrated by animal studies in vitro [3, 4] and in vivo [5, 6], sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
222
3
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(248 citation statements)
references
References 36 publications
21
222
3
2
Order By: Relevance
“…Theta networks of memory encoding and retrieval. Given strong evidence in the literature for synchronous memory effects in the theta band (33)(34)(35)(36)(37), we first sought to characterize the detailed structure of theta networks in the MTL. To do this, we asked whether any regions acted as "hubs" of the MTL by computing the node strength for each region, using theta PLV connection weights.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Theta networks of memory encoding and retrieval. Given strong evidence in the literature for synchronous memory effects in the theta band (33)(34)(35)(36)(37), we first sought to characterize the detailed structure of theta networks in the MTL. To do this, we asked whether any regions acted as "hubs" of the MTL by computing the node strength for each region, using theta PLV connection weights.…”
Section: Resultsmentioning
confidence: 99%
“…The extent to which different frequencies underlie neural synchronization in memory therefore remains an open question, though converging lines of evidence strongly suggest the most prominent connectivity effects occur at low frequencies (33)(34)(35)(36)(37). Moreover, no studies have deeply considered how observations of within-MTL synchronization reflect an experimenter's choice of connectivity metric, including those that are designed to limit the effects of volumeconducted signals that may affect connectivities measured across relatively short distances (38).…”
Section: Introductionmentioning
confidence: 99%
“…Because this oscillatory dynamic was measured with EEG in the scalp of the participants, interpreting the contribution of different cortical sources may be done cautiously. Several works have shown that memory encoding and retrieval is supported by an increased synchronization of slow oscillatory activity (3-8 Hz), notably in the medial temporal lobe (Heusser, Poeppel, Ezzyat, & Davachi, 2016;Clouter, Shapiro, & Hanslmayr, 2017;Burke et al, 2014;. Alternatively, an increase of such activity in the frontal medial electrodes is also a strong correlate of the higher recruitment of cognitive control mechanisms (Cavanagh & Frank, 2014;Mückschel, Dippel, & Beste, 2017;Eschmann, Bader, & Mecklinger, 2018), that may also occur during the TNT procedure.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility may be that RPEs 370 enhance theta phase synchronization. In line with such a view, experimentally induced theta 371 synchronization between visual and auditory modalities improved multimodal stimulus memories 372 (Clouter, Shapiro, & Hanslmayr, 2017), and theta phase synchronization in such a paradigm (as 373 measured via EEG) predicts memory performance on a trial-by-trial basis (Wang, Clouter, Chen, Shapiro, 374 & Hanslmayr, 2018) . Therefore, theta synchronization between relevant brain areas may play the role 375 of efficiently cementing memory information.…”
Section: Although Rpe-dependent Changes In Connectivity Profiles Havementioning
confidence: 92%